Unmasked Androids: Staring Faces in Science Fiction Cinema - Leal, João (Cinémas)

(untitled) (Cinémas, 2017)
This article examines the actor’s performance of android characters in science fiction films. The author discusses how the cinematic android stresses conflicts between identity and expression, acting and performance, face and mask—conflicts that culminate in the recurring visual motif of the “unmasking” of the android to reveal its uncanny gaze. From A Clever Dummy (1917) to Blade Runner 2049 (2017), this article analyzes some of the narrative and aesthetic strategies that transform the human actor into an inhuman character, also pointing to early manifestations of the figure of the android in Western culture and to some of its recent developments through the use of videographic masks in the work of artists Otávio Donasci, Tony Oursler and Denis Marleau.